GENES DETERMINING COLORATION OF DIFFERENT ORGANS IN WHEAT - E. K. Khlestkina (Вавиловский журнал генетики и селекции)
Coloration of some wheat organs may be of adaptive significance. Coloration traits are widely used in wheat taxonomy and variety identification. They also provide a suitable model for genetic and molecular studies. Here, data on chromosome location, genetic mapping, and structural and functional organization of all known genes determining coloration in wheat are reviewed. To date, thirty genes determining coloration in wheat have been mapped. These genes are represented mainly by homoeologous loci in the A, B and D genomes, and most of them are located in the 1S0.8 and 7S0.4 gene-rich regions of wheat genome. Comparative mapping in cereals shows that some orthologous genes determining coloration occur in a few species (homoeologous series Rg has been found in wheat and Aegilops only, and R, in wheat, Aegilops and rye), whereas others (genes determining anthocyanin pigmentation) widely occur in Poaceae. The data on comparative mapping together with the results of recent studies dedicated to cloning and functions of genes determining coloration in wheat suggest that these genes belong to the Myb- and Myc-like families of genes, encoding transcriptional activators for structural genes involved in plant flavonoid pigments biosynthesis.